1993
DOI: 10.1007/bf02294829
|View full text |Cite
|
Sign up to set email alerts
|

Ability estimation for conventional tests

Abstract: item response theory, ability estimation, reliability,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
0
3

Year Published

1998
1998
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 6 publications
6
31
0
3
Order By: Relevance
“…Therefore, to get a more quantitative evaluation of the statistical properties of the Bayesian item selection criteria relative to the maximuminformation criterion, a simulation study was run. The results for the item selection criteria in this paper complement earlier results reported for Bayesian and maximum-likelihood ability estimation for conventional linear tests (Kim & Nicewander, 1993;Warm, 1989) and adaptive tests (Warm, 1989).…”
Section: Large-sample Equivalencesupporting
confidence: 83%
“…Therefore, to get a more quantitative evaluation of the statistical properties of the Bayesian item selection criteria relative to the maximuminformation criterion, a simulation study was run. The results for the item selection criteria in this paper complement earlier results reported for Bayesian and maximum-likelihood ability estimation for conventional linear tests (Kim & Nicewander, 1993;Warm, 1989) and adaptive tests (Warm, 1989).…”
Section: Large-sample Equivalencesupporting
confidence: 83%
“…This inequality is due to the bias of IRT ability estimates and does not happen for the CTT test scores because they are, by definition, unbiased estimates of true scores (Lord & Novick, 1968). Previous research (Kim & Nicewander, 1993;Lord, 1983;Samejima, 1994;Warm, 1989) showed that this bias occurs for any of the ability estimators developed so far, including the ML, MAP, and EAP estimators. However, as discussed in detail later in this paper, most of the previous studies did not pay much attention to the possible inequality between the ρ 2 θθ and ρθθ , presenting formulas for the IRT coefficient by adopting only one of the two definitions of the reliability coefficient.…”
Section: Introductionmentioning
confidence: 94%
“…• des tests comportant n = 11, 31 et 101 items, à réponses 0 ou 1 ; • le paramètre ai a été généré selon une distribution Gamma(10 ; 0,1), produisant des valeurs de caractéristiques µ = 1, σ 2 = 0,100, γ1 = 0,632 et γ2 = 0,600 (pour γ1 et γ2, voir (3)), soit des valeurs plausibles dans le domaine des applications TRI ; les valeurs ai présentées dans le petit exemple à 5 items ci-dessus sont représentatives ; • le paramètre bi a été étalé régulièrement de b1 = -3,5 à bn = +3,5 par intervalles égaux à 7 / (n-1) ; cette structure représente un test équilibré, de niveau de difficulté modéré selon Kim et Nicewander (1993) ; • le paramètre a été étalé régulièrement de = -3,5 à = 3,5 par intervalles de 0,1, plutôt que d'être généré par le biais d'une variable de loi normale (2). Les ingrédients du modèle TRI à deux paramètres étant ainsi définis, le programme informatique simulait alors des protocoles aléatoires répondant à ce contexte.…”
Section: Conditions Et Paramètres De L'étudeunclassified
“…Cette corrélation globale donne un léger avantage à l'estimateur BME, tandis le score brut X se tient tout près des autres, comme il a souvent été démontré (Kim et Nicewander, 1993;Galdin et Laurencelle, 2010). Nous avons donc établi les fonctions de régression linéaire « = b⋅ + a » pour les issus de chacun de nos Figure 3.…”
Section: Prédiction Linéaire à Partir Du Vraiunclassified